2012
DOI: 10.3109/03009734.2012.707253
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea syndrome (OSAS) and hypertension: Pathogenic mechanisms and possible therapeutic approaches

Abstract: Obstructive sleep apnea syndrome (OSAS), a chronic condition characterized by collapse of the pharynx during sleep, has been increasingly recognized as a health issue of growing importance over the last decade. Recently emerging evidence suggests that there is a causal link between OSAS and hypertension, and hypertension represents an independent risk factor in OSAS patients. However, the pathophysiological basis for patients with OSAS having an increased risk for hypertension remains to be elucidated. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 165 publications
(93 reference statements)
2
63
0
3
Order By: Relevance
“…10,11 In the present study, the prevalence of hypertension in all patients with OSAHS (50.5%) was significantly higher than that in controls (30.4%) and increased with the severity of OSAHS, which is consistent with previous reports. 2 In addition, AHI and LS a O 2 were closely related to BP values, with daytime, evening, night-time and morning MBP values rising with increasing AHI and decreasing LS a O 2 after controlling for related confounders.…”
Section: Discussionsupporting
confidence: 94%
“…10,11 In the present study, the prevalence of hypertension in all patients with OSAHS (50.5%) was significantly higher than that in controls (30.4%) and increased with the severity of OSAHS, which is consistent with previous reports. 2 In addition, AHI and LS a O 2 were closely related to BP values, with daytime, evening, night-time and morning MBP values rising with increasing AHI and decreasing LS a O 2 after controlling for related confounders.…”
Section: Discussionsupporting
confidence: 94%
“…[18] The Bogalusa heart cohort study[29] concluded that low birth weight was significantly associated with the development of hypertension later in life. This is in accord with the finding in our study which revealed low birth weight as a significant predictor of prehypertension.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Although studies have proven OSA as an independent risk for hypertension, present study demonstrates that severity of OSA correlates with severity of hypertension. 20,21 Severe hypertension was associated with higher AHI as compared to mild and moderate hypertension. Presently there are a couple of sets of defining criteria for metabolic syndrome set out by two different sources-the International Diabetes Federation and the revised National Cholesterol Education Program (NCEP).…”
Section: Discussionmentioning
confidence: 99%